Aquatic macroinvertebrates and ecological characterization of freshwater environments in the area of influence of the PERU LNG gas pipeline in the departments of Ica and Huancavelica - Arana Maestre, Jerry (2017)
Fifteen sampling stations were evaluated in streams and rivers in the influence area of the pipeline PERÚ LNG in the departments of Ica and Huancavelica, for this physicochemical parameters of water were taken, habitat type described and aquatic macroinvertebrates were collected. The results of physicochemical parameters were acceptable to the development of aquatic macroinvertebrates, with dissolved oxygen values below the legal regulations in the Matagente and Pisco rivers during the dry season (May, 2010), which also aquatic macroinvertebrates were composed of 34 taxa, with a 3671 total abundance of organisms/m2, unlike the wet season (November, 2010), where aquatic macroinvertebrates were composed of 26 taxa, with a total abundance of 1623 organisms/m2. The most representative organisms were arthropods, mainly those belonging to the class Insecta. The stations between 3985 and 4210 meters above sea level had higher taxa richness, because they had more appropriate for the development of the benthic community as optimal concentrations of dissolved oxygen and greater variety of substrates conditions. According to the Andean Biotic Index (ABI), water quality ranged from bad to good for both seasons. In addition to the pipeline gas, the impacts observed in the study area were stockbreeding, agriculture, mining and organic discharges from towns located on the banks of water bodies assessed.